RUANGKASA: A Space for Children’s Creativity - Ilham Ruser; Syamsuyurnita Syamsuyurnita; Emilia Febrianti Saragih; Juni Warohmah; Lesterina Pasaribu; Meilan Rahmah Denny Lubis; Nurainun Ulfa Dalimunthe (Al'Adzkiya International of Education and Sosial (AIoES) Journal, 2023)
The creativity space activities for the nation's children aim to educate utilization goods used/trash become goods useful and selling value, apart from that, to instill a sense of nationalism, caring, creativity and empathy for children starting from an early age and to educate and familiarize children with being able to work in groups or collaboratively . This program will have benefits if the expected goals can be achieved. took the target subject of developing creativity in children aged 7 to 15 years in a learning house on the banks of the Deli river because it considers the importance of providing environmental awareness and instilling good character in the younger generation, especially children who live and are on the banks of the river. Through this training, children can learn various new skills and hone their talents. Participation in children's work activities can increase children's self-confidence and build social skills. Children are able to produce unique and creative works with the right support and guidance. Children's work training can also be a forum for teaching children values such as cooperation, perseverance and responsibility.